The Influence Of Seed Quantity Per Planting Hole On The Agronomics Of Soybean Variety Dena 1 Under Different Lighting Conditions - Nugraha Ramadhan (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2024)
Expansion of soybean cultivation by utilizing land beneath tree canopies and adjusting plant populations can be considered as an alternative to increase national soybean production. The objective of this research is to examine the influence of seed quantity per planting hole on the agronomics of soybean variety Dena 1 under different lighting conditions. This study was conducted from August to November 2023 at the Experimental Garden of the Faculty of Agriculture, Andalas University. The experimental design used was a Completely Randomized Design (CRD) with two factors and three replications. The first factor was lighting conditions, while the second factor was the quantity of seeds per planting hole. Soybean plants under unshaded conditions showed the best influence on plant height, stem diameter, as well as an increase in pod number and percentage of filled pods. The interaction between the treatment of seed quantity per planting hole and different lighting conditions influenced the seed weight per plot, where planting two seeds per planting hole under unshaded conditions yielded the best result at 280.56 g.